The Degree of teachers contribute to developing some social skills among first-year students is essential from their point of view" A field study in the city of Tartous" (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the current research is to know the degree of the teacher’s contribution to the development of some social skills (cooperation skill, participation skill, law-abiding skill) among students of the first cycle of basic education from their point of view, as well as identifying the differences in the views of the sample members of teachers about their role in developing  Some social skills of students according to the variables: gender, educational and educational qualifications, and number of years of experience.  The researcher used the descriptive approach, and the tool was a questionnaire (prepared by the researcher, judged by specialists, and studied the psychometric characteristics), which was applied to a sample of (194) male and female teachers in the schools of the first cycle of basic education.         The results of the research showed that the degree of the teacher’s contribution to the development of some social skills (cooperation skill, participation skill, law-abiding skill) among students of the first cycle of basic education from their point of view was medium on the axis (cooperation skill, participation skill), while it was high on the commitment axis  by laws and regulations.  And that there is no difference in the teachers’ views about the degree of their contribution to the development of some social skills according to the gender variable, while there is a difference in their views according to the educational qualification variable (in favor of holders of the educational qualification diploma), and according to the variable of years of experience (in favor of those who have experience more than  10 years).